The AtSUC1 sucrose carrier may represent the osmotic driving force for anther dehiscence and pollen tube growth in Arabidopsis. - Stadler, Ruth; Truernit, Elisabeth; Gahrtz, Manfred; Sauer, Norbert (Plant Journal, 1999)
The Arabidopsis AtSUC1 protein has previously been characterized as a plasma membrane H+-sucrose symporter. This paper describes the sites of AtSUC1 gene expression and AtSUC1 protein localization and assigns specific functions to this sucrose transporter in anther development and pollen tube growth. RNase protection assays revealed AtSUC1 expression exclusively in floral tissue, which was confirmed by analyses of AtSUC1 promoter-beta-glucuronidase (GUS) plants. In situ hybridizations identified AtSUC1 expression in anther connective tissue, in funiculi and in fully developed pollen grains. Indirect immuno-fluorescence analyses with anti-AtSUC1 antiserum confirmed AtSUC1 protein localization in the connective tissue and funiculi. In mature pollen grains, however, despite high AtSUC1 mRNA levels no AtSUC1 protein was found. Only after pollination of stylar papillae was AtSUC1 protein detected inside the pollen and later inside the growing pollen tubes, suggesting a translation of pre-existing AtSUC1 mRNA after pollination. Pollen germination analyses underlined the important role of sucrose for pollen tube growth. The data presented suggest a role of AtSUC1 in the controlled dehiscence of Arabidopsis anthers. It is postulated that an important function of AtSUC1 is the cell-specific modulation of water potentials.